Selected Factors Governing International Financial Integration – Special Reference to Indian Economy with BRICS - S. , Santosh Kumar; V. , Sachithanantham (International Journal of Psychosocial Rehabilitation, 2020)
BRICS has been growing tremendously among all other countries. The 2008 financial crisis has created an impact on cross-border investment with respect to focusing on exchange rate fluctuations and investment decision-making. The impact of exchange rate determination on both the interest rate and inflation rate together leading to a major factor of international financial integration has been professionally reviewed and empirically proved as a basic factor by various authors in different areas of study. Apart from interest rates and inflation rates, crude oil prices have also equally influenced the country’s economy. International financial integration is one of the major factors influencing the country’s economic development and financial status. Selected factors such as purchasing power parity, interest rate parity, and crude oil prices have been considered to analyze the financial integration with a special reference to the Indian economy with BRICS. This paper argues about selected crucial factors governing the international financial integration of the Indian economy along with BRICS for a period of 10 years (2008–2017). The study is carried out by ex post facto-type research design. The objective of the study is to identify the inflation rate, interest rate, and crude oil price fluctuation of India along with BRICS. The study uses trend analysis as a statistical tool and hypothesis testing to prove the financial integration of the Indian economy with respect to selected countries. The findings will act as a catalyst towards promoting international financial integration effectively.